The Influence Of Service Quality, Price Perception, And Customer Reviews On Customer Loyalty At Jne Pasuruan - Handika, Arya Dharma Syahputra; Pudjoprastyono, Hery (UNIVERSITAS PAKUAN, 2025)
The challenge faced by courier companies like JNE Pasuruan is how to maintain customer loyalty amidst increasing competition. Customer loyalty is greatly influenced by several factors, one of which is the quality of service provided, the price perception that aligns with the value received, and reviews from other customers that can impact customer loyalty. The objective of this study is to investigate the impact of service quality, price perception, and customer reviews on customer loyalty at JNE Pasuruan. The research employs a quantitative approach with a survey method, involving 75 respondents who are JNE Pasuruan customers. Data were collected using questionnaires and analyzed through the Partial Least Squares (PLS) technique. The study tested validity, reliability, and hypotheses to determine the relationships between the variables studied. The results show that: (1) Service quality significantly affects customer loyalty at JNE Pasuruan, where good service increases customer satisfaction and loyalty, (2) Price perception has a positive effect on customer loyalty, where prices considered fair and matching the quality of service increase loyalty, and (3) Customer reviews have a significant impact on customer loyalty, where positive reviews from other customers enhance trust and the decision to continue using JNE’s services. Based on these findings, it is recommended that JNE Pasuruan continue to improve service quality, maintain affordable pricing, and effectively manage customer reviews to maintain customer loyalty